Analysis of the use of Google Classroom, in the students of System Engineering of the Instituto Tecnologico de Mexicali - Ocampo, Jesus Francisco Gutierrez; M.C. Jose Antonio Camaño Quevedo; M.C. Corina Araceli Ortiz Perez; Berenice Yanet Muñiz Castillo (European Journal of Multidisciplinary Studies, 2017)
.Google Classroom is a new tool that allows the student to work online with various file formats such as MP3 audios, Videos, Photos, images, PDF files, which are intended to be a valuable tool in the teaching process The objective of this quantitative research is to measure the impact on the users of the systems engineering career of the Instituto Tecnológico de Mexicali with 402 student enrolled and to make a diagnosis, based on the results of a survey applied to a 71 students of the career of Systems Engineering of the Instituto Tecnológico de Mexicali.
Keywords: Google, Classroom, Ingenieria de sistemas.